Analytical estimation of influence of dynamic parameters of testing machine fluid drive on accuracy of test operations - D. N. Andrianov; N. V. Andrianov (Литьë и металлургия, 2002)
The article takes up the processes, occuring at the extention test of metals. The mathematical model of the system «tensile-testing machine hidraulicaly operated- sample—testing mode» is derived. There is shown analytic dependence of absolute and ratio dynamic error of test operations on the parameters of machine, substance and size of the tested sample, testing mode. There are given conclusions and recommendations on reducing of test operations error.